Rubber composition and tire
A rubber composition with 70% natural rubber, silica, and a cyclic polyol compound with a hydrocarbyl group addresses cut resistance and elongation fatigue issues, enhancing tire performance by preventing agglomeration and improving abrasion resistance.
Patent Information
- Application Number
- JP2021565408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-18
- Filing Date
- 2020-11-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-11-24
AI Technical Summary
Existing rubber compositions used in tires and other rubber articles suffer from inadequate cut resistance and elongation fatigue resistance, particularly under severe conditions, and agglomeration issues arise when incorporating compounds like sorbitol to improve cut resistance.
A rubber composition comprising 70% natural rubber, silica filler, and a cyclic polyol compound with a hydrocarbyl group, along with optional linear polyhydric alcohol and carbon black, enhances cut resistance and maintains good elongation fatigue resistance by minimizing self-aggregation.
The composition achieves superior cut resistance and elongation fatigue resistance, with improved reinforcing properties and abrasion resistance, while preventing agglomeration and maintaining workability.
Smart Images

Figure 0007601790000001 
Figure 0007601790000002 
Figure 0007601790000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition and a tire. [Background technology]
[0002] In order to improve the functions of a rubber composition and a crosslinked rubber obtained by crosslinking the rubber composition, various components are also used as additives for the rubber composition. For example, Patent Document 1 discloses a technique for improving the adhesion in vulcanization adhesion with steel cord and the hardness of rubber by blending 0.5 to 10 parts by weight of (B) carbohydrate, 0.5 to 10 parts by weight of (C) methoxylated methylol melamine resin, and 0.05 to 1 part by weight of (D) cobalt carboxylate salt with 100 parts by weight of (A) rubber selected from natural rubber, styrene-butadiene copolymer rubber, butadiene rubber, isoprene rubber, acrylonitrile-butadiene copolymer rubber, chloroprene rubber, butyl rubber, and halogenated butyl rubber. Furthermore, Patent Document 2 discloses a technology that aims to achieve both abrasion resistance and wet performance and performance on ice by incorporating a specific diene rubber and silica having a glass transition point and a CTAB adsorption specific surface area within specific ranges in a rubber composition.
[0003] However, the technology disclosed in Patent Document 1 is poor in cut resistance and abrasion resistance under severe conditions (high severity conditions), and further improvement is desired in consideration of application to rubber articles such as tires. In addition, with the technology disclosed in Patent Document 2, since the rubber composition has low elasticity, sufficient effects are not obtained with respect to the cut resistance and abrasion resistance of the rubber composition after vulcanization, and further improvements are desired.
[0004] Therefore, in recent years, a technique has been developed in which a compound having a polyol structure, such as sorbitol, is added to a rubber composition in order to improve the cut resistance of the rubber composition. This technology makes it possible to improve cut resistance compared to conventional techniques without compromising physical properties such as low heat buildup. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 07-118457 [Patent Document 2] JP 2016-47888 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the technology of incorporating a compound such as sorbitol into a rubber composition, there is a risk that agglomerates derived from the compound are generated, and the presence of the agglomerates may cause a problem in that the elongation fatigue properties of the rubber are deteriorated. Therefore, further improvement was desired.
[0007] Therefore, an object of the present invention is to provide a rubber composition having excellent cut resistance while maintaining good elongation fatigue properties. Another object of the present invention is to provide a tire having excellent cut resistance while maintaining good elongation fatigue properties. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to improve crack resistance and abrasion resistance, and have found that by incorporating a small amount of a cyclic polyol compound having a hydrocarbyl group into a rubber composition containing a large amount of natural rubber as a rubber component, the strength of the rubber can be increased while suppressing aggregation in the rubber composition, and as a result, it is possible to improve cut resistance while maintaining good elongation fatigue properties.
[0009] That is, the rubber composition of the present invention is characterized by comprising a rubber component containing 70% by mass or more of natural rubber, a filler containing at least silica, and 0.1 to 2 parts by mass of a cyclic polyol compound having a hydrocarbyl group per 100 parts by mass of the natural rubber in the rubber component. By providing the above-mentioned configuration, it is possible to realize excellent cut resistance while maintaining good elongation fatigue resistance.
[0010] In the rubber composition of the present invention, the cyclic polyol compound having a hydrocarbyl group is preferably a cyclic polyol compound having a hydrocarbyl ester group, since this makes it possible to realize better elongation fatigue properties and cut resistance.
[0011] Furthermore, in the rubber composition of the present invention, the cyclic polyol compound having a hydrocarbyl group preferably has two or more hydroxyl groups, since this allows for the realization of better cut resistance.
[0012] In addition, in the rubber composition of the present invention, the hydrocarbyl group-containing cyclic polyol compound is represented by the following formula (1): [ka] [wherein A is a hydrocarbyl ester group having 6 to 30 carbon atoms or a hydrocarbyl ether group having 6 to 30 carbon atoms, and X1, X2, X3 and X4 are each independently -OH or -R (wherein -R is -H or -CH2OH), provided that at least three of X1, X2, X3 and X4 are -OH] is preferred, and it is more preferred that the hydrocarbyl group moiety of A in formula (1) has 12 to 24 carbon atoms in the cyclic polyol compound having a hydrocarbyl group. This is because better elongation fatigue property and cut resistance can be achieved.
[0013] Furthermore, in the rubber composition of the present invention, the melting point of the cyclic polyol compound having a hydrocarbyl group is preferably 40 to 100° C. This is because cut resistance at high temperatures can be further improved.
[0014] Furthermore, in the rubber composition of the present invention, the content of the linear polyhydric alcohol is preferably 0.5 to 6 parts by mass per 100 parts by mass of the natural rubber in the rubber component, because this allows for realizing better cut resistance while maintaining good elongation fatigue properties.
[0015] In addition, in the rubber composition of the present invention, the content of the silica is preferably 5 to 100 parts by mass per 100 parts by mass of the rubber component, because this allows for achieving better cut resistance and reinforcement without impairing processability.
[0016] Furthermore, in the rubber composition of the present invention, it is preferable that the filler further contains carbon black, and the content of the carbon black relative to the content of the silica is preferably in a mass ratio of 0.1 to 4. This is because low heat build-up and abrasion resistance can be improved.
[0017] Moreover, the rubber composition of the present invention preferably further contains a silane coupling agent, and the content of the silane coupling agent relative to the content of the silica is preferably 0.2 or less in mass ratio, because this allows for the realization of better cut resistance.
[0018] Furthermore, the rubber composition of the present invention preferably further contains polyethylene glycol, since this can further improve the workability.
[0019] The tire of the present invention is characterized in that the above-mentioned rubber composition is used in the tread portion. By providing the above-mentioned configuration, it is possible to realize excellent cut resistance while maintaining good elongation fatigue resistance.
[0020] Moreover, the tire of the present invention is preferably a tire for a construction vehicle, since the effect of improving the elongation fatigue property and the cut resistance is significant. Effect of the Invention
[0021] According to the present invention, it is possible to provide a rubber composition having excellent cut resistance while maintaining good elongation fatigue properties. Also, according to the present invention, it is possible to provide a tire having excellent cut resistance while maintaining good elongation fatigue properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the embodiments of the present invention will be specifically illustrated and described. <Rubber composition> The rubber composition of the present invention is a rubber composition including a rubber component containing 70% by mass or more of natural rubber, a filler containing at least silica, and 0.1 to 2 parts by mass of a cyclic polyol compound having a hydrocarbyl group, based on 100 parts by mass of the rubber component.
[0023] (Rubber component) The rubber component contained in the rubber composition of the present invention contains 70% by mass or more of natural rubber (NR). By containing 70% by mass or more of natural rubber, excellent cut resistance, reinforcing properties, abrasion resistance, etc. can be obtained by using the natural rubber together with a cyclic polyol compound having a hydrocarbyl group described later.
[0024] The reason why the content of natural rubber in the rubber component is set to 70% by mass or more is that by using it together with a cyclic polyol compound having a hydrocarbyl group, which will be described later, it is possible to reliably improve cut resistance and abrasion resistance. From the same viewpoint, the content of natural rubber in the rubber component is preferably 80% by mass or more, and more preferably 90% by mass or more.
[0025] The rubber component may contain any synthetic rubber in addition to the natural rubber. For example, from the viewpoint of obtaining excellent cut resistance and abrasion resistance, it is preferable that the rubber component contains a diene-based synthetic rubber.
[0026] Examples of the diene synthetic rubber include synthetic polyisoprene (IR), styrene-butadiene copolymer rubber (SBR), polybutadiene rubber (BR), etc. The diene synthetic rubber in the rubber component may be contained alone or as a blend of two or more kinds. The rubber component may also contain non-diene synthetic rubber depending on the required performance.
[0027] (Cyclic polyol compound having hydrocarbyl group) In addition to the above-mentioned rubber component, the rubber composition of the present invention further contains 0.1 to 2 parts by mass of a cyclic polyol compound having a hydrocarbyl group per 100 parts by mass of the natural rubber in the rubber component. The cyclic polyol compound having a hydrocarbyl group contained in the rubber composition can greatly improve the cut resistance of the rubber composition of the present invention. In addition, by increasing the interaction between the rubber molecules of the rubber component and the agent described below, the physical properties of the rubber after crosslinking can be homogenized, and as a result, the reinforcement and abrasion resistance can also be improved. Furthermore, since the cyclic polyol compound having a hydrocarbyl group has fewer hydrophilic sites than compounds such as sorbitol, self-aggregation in the rubber composition can be suppressed, and as a result, the elongation fatigue properties of the rubber composition can be well maintained.
[0028] The content of the hydrocarbyl group-containing cyclic polyol compound is 0.1 to 2 parts by mass per 100 parts by mass of the natural rubber, but if the content is less than 0.1 parts by mass per 100 parts by mass of the natural rubber, the amount of the cyclic polyol compound is so small that the cut resistance is not sufficiently improved and the elongation fatigue property is not sufficiently improved. On the other hand, if the content of the hydrocarbyl group-containing cyclic polyol compound exceeds 2 parts by mass per 100 parts by mass of the natural rubber, the amount of the cyclic polyol compound becomes too large, which may cause self-aggregation in the rubber composition and deteriorate the elongation fatigue property. From the same viewpoint, the content of the hydrocarbyl group-containing cyclic polyol compound is preferably 0.1 to 1.5 parts by mass, and more preferably 0.3 to 1.2 parts by mass, based on 100 parts by mass of the natural rubber.
[0029] Here, the cyclic polyol compound having a hydrocarbyl group preferably has two or more hydroxyl groups, and more preferably has three or more hydroxyl groups, because the presence of many hydroxyl groups leads to a stronger interaction between the rubber component and the additives, thereby realizing better cut resistance.
[0030] Furthermore, the cyclic polyol compound having a hydrocarbyl group is preferably a cyclic polyol compound having a hydrocarbyl ester group, since this allows for the realization of better elongation fatigue resistance and cut resistance.
[0031] Furthermore, in order to realize more excellent elongation fatigue resistance and cut resistance, the cyclic polyol compound having a hydrocarbyl group is represented by the following formula (1): [ka] It is more preferable that the compound is represented by the following formula:
[0032] In the above formula (1), A is a hydrocarbyl ester group having 6 to 30 carbon atoms or a hydrocarbyl ether group having 6 to 30 carbon atoms, and the number of carbon atoms in the hydrocarbyl group portion of A is preferably 12 to 24. When the number of carbon atoms in the hydrocarbyl group portion of A in formula (1) is in the range of 12 to 24, cut resistance is further improved while maintaining good elongation fatigue properties. In addition, in the formula (1), it is preferable that the first atom from the ring portion (i.e., the atom bonded to the ring) or the second atom from the ring portion is an oxygen atom. Examples of A in which the first atom from the ring portion is an oxygen atom include groups represented by -O-A' and -O-CO-A'', and examples of A in which the second atom from the ring portion is an oxygen atom include groups represented by -CH2-O-A'' and -CH2-O-CO-A''', where A' is preferably a hydrocarbyl group having 6 to 30 carbon atoms, A'' is a hydrocarbyl group having 5 to 29 carbon atoms, and A''' is a hydrocarbyl group having 4 to 28 carbon atoms, and it is more preferable that A', A'' and A''' are hydrocarbyl groups having 12 to 24 carbon atoms.
[0033] In the formula (1), X1, X2, X3, and X4 are each independently -OH or -R (wherein -R is -H or -CH2OH), provided that at least three of X1, X2, X3, and X4 are -OH. When three or more of X1, X2, X3, and X4 are -OH, the cut resistance of the rubber composition is further improved.
[0034] Furthermore, among the compounds represented by the above formula (1), compounds represented by the following formula (2) or formula (3): [ka] [ka] More preferred are compounds represented by the above formula (2), and particularly preferred are compounds represented by the above formula (2). In the formulas (2) and (3), n is a natural number, and is preferably in the range of 11 to 23. By incorporating a compound represented by the above formula (2) or (3) as the modified cyclic polyol compound, it is possible to further improve cut resistance while maintaining good elongation fatigue properties.
[0035] The cyclic polyol compound having a hydrocarbyl group is not particularly limited, but can be obtained, for example, by reacting a polyol compound such as sorbitol, sorbitan, glucose, or fructose with an aliphatic alcohol such as octanol, decanol, dodecanol, tetradecanol, or hexadecanol, or an aliphatic carboxylic acid such as lauric acid, myristic acid, palmitic acid, stearic acid, or oleic acid.
[0036] Specific examples of the cyclic polyol compound having a hydrocarbyl group include ester compounds such as sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate, and ether compounds such as octyl-β-D-glucopyranoside, decyl-β-D-glucopyranoside, dodecyl-β-D-glucopyranoside, tetradecyl-β-D-glucopyranoside, and hexadecyl-β-D-glucopyranoside. These compounds may be used alone or in combination of two or more. Among these compounds, from the viewpoint of achieving both high levels of elongation fatigue resistance and cut resistance, the cyclic polyol compound having a hydrocarbyl group is preferably a sorbitan monoester.
[0037] Furthermore, the melting point of the cyclic polyol compound having a hydrocarbyl group is preferably 40 to 100° C., and more preferably 45 to 90° C. When the melting point of the cyclic polyol compound having a hydrocarbyl group is 100° C. or lower, the solubility during kneading and vulcanization reaction can be improved, and when the melting point is 40° C. or higher, the cut resistance at high temperatures can be improved.
[0038] (Linear polyhydric alcohol) Moreover, the rubber composition of the present invention preferably further contains a linear polyhydric alcohol in addition to the above-mentioned rubber component and cyclic polyol compound having a hydrocarbyl group. By further containing the linear polyhydric alcohol, the cut resistance of the rubber composition can be further improved.
[0039] Here, the linear polyhydric alcohol preferably has three or more hydroxyl groups, and more preferably has five or more hydroxyl groups, because the linear polyhydric alcohol has many hydroxyl groups, which makes it possible to realize better cut resistance and abrasion resistance.
[0040] Furthermore, the melting point of the linear polyhydric alcohol is preferably less than 170° C. This is because it is possible to improve the solubility during kneading and vulcanization reactions. From the viewpoint of blocking properties, the melting point of the linear polyhydric alcohol is preferably 40° C. or higher.
[0041] Here, the type of the linear polyhydric alcohol is not particularly limited, and any known linear polyhydric alcohol can be used. For example, from the viewpoint of realizing better cut resistance, it is preferable to use at least one selected from the group consisting of xylitol, sorbitol, mannitol, and galactitol.
[0042] The content of the linear polyhydric alcohol is preferably 0.5 to 6 parts by mass, and more preferably 1 to 4 parts by mass, per 100 parts by mass of natural rubber in the rubber component. When the content of the linear polyhydric alcohol is 0.5 part by mass or more per 100 parts by mass of natural rubber, better cut resistance can be obtained, and when the content is 6 parts by mass or less per 100 parts by mass of natural rubber, deterioration in elongation fatigue property caused by aggregation of the linear polyhydric alcohol can be suppressed.
[0043] (Filler) The rubber composition of the present invention contains the above-mentioned rubber component, cyclic polyol compound, and linear polyhydric alcohol as an optional component, as well as a filler containing at least silica. By including a filler containing silica together with the rubber component, properties such as low cut resistance and abrasion resistance can be improved.
[0044] Here, examples of the type of silica include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc., and among these, wet silica is preferred. These silicas may be used alone or in combination of two or more kinds. The wet silica may be precipitated silica, which is obtained by growing primary silica particles by reacting a reaction solution at a relatively high temperature in a neutral to alkaline pH range in the early stages of production, and then controlling the reaction solution to the acidic side to aggregate the primary particles.
[0045] The silica is not particularly limited, but may be, for example, a silica having a CTAB specific surface area (cetyltrimethylammonium bromide adsorption specific surface area) of 70 m 2 / g or more, 250m 2 The CTAB specific surface area is a value measured in accordance with ASTM D3765-92. However, the adsorption cross section per molecule of cetyltrimethylammonium bromide on the silica surface can be set to 0.35 nm 2 The specific surface area (m2) calculated from the amount of CTAB adsorbed is 2 / g) is the specific surface area of CTAB. The BET specific surface area of the silica is 100 m 2 / g or more, 250m 2 The BET specific surface area is a specific surface area determined by a BET method, and in the present invention, can be measured in accordance with ASTM D4820-93.
[0046] The content of the silica is preferably 5 to 100 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 10 to 45 parts by mass, based on 100 parts by mass of the rubber component. When the content of the silica is 10 parts by mass or more based on 100 parts by mass of the rubber component, cut resistance and handling stability can be further improved, and when the content is less than 50 parts by mass, deterioration of processability and low rolling resistance of the rubber composition can be suppressed.
[0047] The filler may further contain carbon black in addition to the silica described above. By containing carbon black, the reinforcement property and abrasion resistance of the tire can be further improved. The carbon black is not particularly limited, and examples thereof include GPF, FEF, HAF, N339, IISAF, ISAF, and SAF grade carbon blacks, and have a nitrogen adsorption specific surface area (N2SA, measured in accordance with JIS K 6217-2:2001) of 20 to 250 m 2 / g of carbon black can be used. Among these, ISAF and SAF grade carbon black are preferred from the viewpoint of improving the abrasion resistance of the rubber composition. These carbon blacks may be used alone or in combination of two or more.
[0048] The amount of carbon black is not particularly limited, but is preferably 5 to 100 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 10 to 40 parts by mass, per 100 parts by mass of the rubber component. If the amount of carbon black is 5 parts by mass or more per 100 parts by mass of the rubber component, cut resistance can be further improved, and if the amount is less than 50 parts by mass, heat buildup can be suppressed.
[0049] Furthermore, the content of the carbon black is not particularly limited, but the content of the carbon black relative to the content of the silica (carbon black content / silica content) is preferably 0.1 to 4, more preferably 0.1 to 0.9, and even more preferably 0.2 to 0.7, in mass ratio. Another preferred example is a ratio of 2 to 4, and more preferably 2.5 to 4. When the mass ratio of the carbon black to the silica content is 0.1 or more, better abrasion resistance and reinforcing properties can be obtained, and when the mass ratio of the carbon black to the silica content is 4 or less, better cut resistance can be obtained without deteriorating the low heat generation properties.
[0050] In addition to the above-mentioned silica and carbon black, the filler may be a compound represented by the following general formula (XX): nM xSiO y zH2O (XX) [wherein M is at least one selected from the group consisting of metals selected from the group consisting of aluminum, magnesium, titanium, calcium, and zirconium, oxides or hydroxides of these metals, and hydrates thereof, or carbonates of these metals; and n, x, y, and z are integers of 1 to 5, integers of 0 to 10, integers of 2 to 5, and integers of 0 to 10, respectively]. Examples of the inorganic compound of the general formula (XX) include alumina (Al2O3) such as γ-alumina and α-alumina, alumina monohydrate (Al2O3·H2O) such as boehmite and diaspore, aluminum hydroxide [Al(OH)3] such as gibbsite and bayerite, aluminum carbonate [Al2(CO3)3], magnesium hydroxide [Mg(OH)2], magnesium oxide (MgO), magnesium carbonate (MgCO3), talc (3MgO·4SiO2·H2O), attapulgite (5MgO·8SiO2·9H2O), titanium white (TiO2), titanium black (TiO 2n-1), calcium oxide (CaO), calcium hydroxide [Ca(OH)2], magnesium aluminum oxide (MgO·Al2O3), clay (Al2O3·2SiO2), kaolin (Al2O3·2SiO2·2H2O), pyrophyllite (Al2O3·4SiO2·H2O), bentonite (Al2O3·4SiO2·2H2O), aluminum silicate (Al2SiO5, Al4·3SiO4·5H2O, etc.), magnesium silicate (Mg2SiO4, MgSiO3, etc.), ke Examples of such inorganic silicates include calcium aluminate (Ca2SiO4, etc.), calcium aluminium silicate (Al2O3·CaO·2SiO2, etc.), calcium magnesium silicate (CaMgSiO4), calcium carbonate (CaCO3), zirconium oxide (ZrO2), zirconium hydroxide [ZrO(OH)2·nH2O], zirconium carbonate [Zr(CO3)2], and crystalline aluminosilicates that contain hydrogen, alkali metals, or alkaline earth metals to compensate for the charge, such as various zeolites. From the viewpoint of the balance between wear resistance and wet performance, the inorganic compound of the general formula (XX) preferably has an average particle size of 0.01 to 10 μm, and more preferably 0.05 to 5 μm.
[0051] Here, the total content of the filler is not particularly limited, but is preferably 20 to 150 parts by mass, more preferably 30 to 120 parts by mass, and particularly preferably 40 to 100 parts by mass, relative to 100 parts by mass of the rubber component. This is because optimizing the amount of the filler can further improve tire properties such as cut resistance, low loss, and abrasion resistance.
[0052] (Other Ingredients) The rubber composition of the present invention may contain, as other components, compounding agents that are commonly used in the rubber industry, in addition to the above-mentioned rubber component, hydrocarbyl group-containing cyclic polyol compound and filler, and linear polyhydric alcohol as an optional component. As for other components, for example, silane coupling agents, crosslinking agents, vulcanization accelerators, polyethylene glycols, softeners, resins, antioxidants, zinc oxide, etc. may be appropriately selected and contained within a range that does not impair the object of the present invention. As these compounding agents, commercially available products may be suitably used.
[0053] In addition, when silica is contained as the above-mentioned filler, it is preferable to further contain a silane coupling agent. This is because it can further improve the effects of cut resistance, reinforcing property, and low loss property due to silica. In addition, the silane coupling agent can be appropriately used as a known one. Examples of the silane coupling agent include bis(3-triethoxysilylpropyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyltetrasulfide, 3-triethoxysilylpropyl Examples of the silane coupling agent include -N,N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-trimethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, 3-trimethoxysilylpropyl methacrylate monosulfide, bis(3-diethoxymethylsilylpropyl)tetrasulfide, 3-mercaptopropyldimethoxymethylsilane, dimethoxymethylsilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, dimethoxymethylsilylpropyl benzothiazolyl tetrasulfide, etc. These silane coupling agents may be used alone or in combination of two or more.
[0054] Furthermore, the content of the silane coupling agent varies depending on the type of silane coupling agent, but is preferably 0.2 or less in mass ratio to the content of silica, more preferably 0.1 or less, and even more preferably 0.05 or less. This is because by reducing the content of the silane coupling agent to 0.2 or less in mass ratio to the content of silica, the cut resistance of the rubber composition can be further improved.
[0055] The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose. For example, sulfur-based crosslinking agents, organic peroxide-based crosslinking agents, inorganic crosslinking agents, polyamine crosslinking agents, resin crosslinking agents, sulfur compound-based crosslinking agents, oxime-nitrosamine-based crosslinking agents, etc. can be mentioned. Among these crosslinking agents, sulfur-based crosslinking agents (vulcanizing agents) are more preferable for rubber compositions for tires. The content of the crosslinking agent is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 0.1 to 20 parts by mass based on 100 parts by mass of the rubber component.
[0056] In addition, when sulfur is used as the crosslinking agent, it is preferable to include a vulcanization accelerator. As the vulcanization accelerator, a conventionally known one can be used, and there is no particular limitation. For example, sulfenamide-based vulcanization accelerators such as CBS (N-cyclohexyl-2-benzothiazylsulfenamide), TBBS (Nt-butyl-2-benzothiazylsulfenamide), and TBSI (Nt-butyl-2-benzothiazylsulfenimide) can be mentioned; guanidine-based vulcanization accelerators such as DPG (diphenylguanidine); thiuram-based vulcanization accelerators such as tetraoctylthiuram disulfide and tetrabenzylthiuram disulfide; and zinc dialkyldithiophosphate. The content is preferably less than the content of the sulfur, and more preferably about 1 to 10 parts by mass per 100 parts by mass of the rubber component.
[0057] It is preferred that the rubber composition of the present invention further contains glycerol monostearate, since this can further improve workability, such as shortening the scorch time and increasing the vulcanization rate during tire production.
[0058] The content of the glycerol monostearate is 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and more preferably 0.5 parts by mass or more, based on 100 parts by mass of the rubber component. If the content is less than 0.1 parts by mass, the effects of the present invention may not be obtained satisfactorily. The content is 3.5 parts by mass or less, preferably 3 parts by mass or less, and more preferably 2.5 parts by mass or less. If the content exceeds 3.5 parts by mass, the scorch time tends to be too short.
[0059] Furthermore, the content of the polyethylene glycol is 0.1 parts by mass or more, preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the rubber component. If it is less than 0.1 parts by mass, the effects of the present invention may not be obtained well. The content is 3.5 parts by mass or less, preferably 3 parts by mass or less, more preferably 2.5 parts by mass or less. If it exceeds 3.5 parts by mass, the scorch time tends to be too short.
[0060] Furthermore, the rubber composition of the present invention may contain a softener in order to increase the flexibility of the rubber and realize better wet performance and ice performance. The softener may be a conventionally known softener, and is not particularly limited. Examples of the softener include petroleum-based softeners such as aroma oil, paraffin oil, and naphthene oil, and vegetable-based softeners such as palm oil, castor oil, cottonseed oil, and soybean oil. When used, one type may be used alone, or two or more types may be appropriately selected from these. When the softener is contained, from the viewpoint of ease of handling, it is preferable to contain, among the above-mentioned softeners, one that is liquid at room temperature such as 25°C, for example, a petroleum-based softener such as aroma oil, paraffin oil, or naphthenic oil.
[0061] Furthermore, the rubber composition of the present invention may contain a resin in order to increase the flexibility of the rubber and realize better wet performance and ice performance. As the resin, various natural and synthetic resins may be used, and specifically, it is preferable to use rosin-based resins, terpene-based resins, petroleum-based resins, phenol-based resins, coal-based resins, xylene-based resins, etc. These resins may be used alone or in combination of two or more.
[0062] The method for producing the rubber composition of the present invention is not particularly limited. For example, the rubber composition of the present invention can be obtained by blending and kneading the above-mentioned rubber component, the filler containing at least silica, the cyclic polyol compound having a hydrocarbyl group, and other components that are optionally blended, by a known method.
[0063] <Tires> The tire of the present invention is characterized in that the above-mentioned rubber composition of the present invention is used in the tread portion of the tire. By applying the rubber composition of the present invention to the tire tread portion, it is possible to realize excellent cut resistance while maintaining good elongation fatigue properties. Here, the tire of the present invention is preferably used as a tire for a construction vehicle, a tire for a truck or a bus, or a tire for an aircraft, because the rubber composition of the present invention used as a material for the tread portion has excellent cut resistance and is advantageous when used as a tire for a construction vehicle.
[0064] The tire of the present invention is not particularly limited except that the rubber composition of the present invention is used in the tread portion of the tire, and can be manufactured according to a conventional method. The gas to be filled in the tire can be normal air or air with an adjusted oxygen partial pressure, or an inert gas such as nitrogen, argon, or helium. EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0066] (Examples 1-1 to 1-2, Comparative Examples 1-1 to 1-3) According to the formulation shown in Table 1, rubber composition samples were prepared by compounding and kneading in a conventional manner. After the obtained samples were subjected to a vulcanization treatment, the following evaluations (1) and (2) were carried out. (Example 1-1, Example 2-1, Comparative Example 1-1, Comparative Examples 2-1 to 2-3) According to the formulation shown in Table 2, rubber composition samples were prepared by compounding and kneading in a conventional manner. After the obtained samples were subjected to a vulcanization treatment, the following evaluations (1) and (2) were carried out. (Examples 3-1 to 3-2, Comparative Example 3-1) According to the formulation shown in Table 3, rubber composition samples were prepared by compounding and kneading in a conventional manner. After the obtained samples were subjected to a vulcanization treatment, the following evaluations (1) and (2) were carried out. (Examples 4-1 to 4-4, Comparative Example 3-1) According to the formulation shown in Table 4, rubber composition samples were prepared by compounding and kneading in a conventional manner. After the obtained samples were subjected to a vulcanization treatment, the following evaluations (1) and (2) were carried out.
[0067] <Evaluation> (1) Cut resistance For each sample of the examples and comparative examples, after vulcanization treatment, a pure shear type test piece was prepared, and a tensile testing device (Shimadzu Corporation) was used to make an incision in the test piece while pulling it, and the state of crack propagation was observed, and the energy release rate (transformation energy) at which the crack propagation rate discontinuously increased was measured. The evaluation was performed by calculating the reciprocal of the transition energy of each measured sample. In Table 1, Examples 1-1 to 1-2 and Comparative Examples 1-2 to 1-3 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 1-1 is set to 100. In Table 2, Example 1-1 is shown as an index value when the reciprocal of the transition energy of the sample of Comparative Example 1-1 is set to 100, Example 2-1 is shown as an index value when the reciprocal of the transition energy of the sample of Comparative Example 2-1 is set to 100, and Comparative Example 2-3 is shown as an index value when the reciprocal of the transition energy of the sample of Comparative Example 2-2 is set to 100. In Table 3, Example 3-1 and Comparative Example 3-2 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 3-1 is set to 100. Furthermore, in Table 4, Examples 4-1 and 4-2 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 4-1 is taken as 100, Examples 4-3 and 4-4 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 4-2 is taken as 100, Examples 4-5 and 4-6 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 4-3 is taken as 100, and Examples 4-7 and 4-8 are shown as index values when the reciprocal of the transition energy of the sample of Comparative Example 4-4 is taken as 100. In Table 4, the transition energy was predicted by multiple regression analysis from the transition energy results of multiple samples in which the sorbitan amount, silica part number, silane part number, monoglyceryl part number, and modulus were independently changed. In addition, the larger the value in Tables 1 to 4, the better the cut resistance.
[0068] (2) Resistance to tension fatigue For each sample of the Examples and Comparative Examples, after a vulcanization treatment, a dumbbell-shaped test piece with a width of 6 mm was prepared, and a tensile test was performed using a tensile tester (Shimadzu Corporation) by repeatedly tensioning the test piece at 5 Hz with a 0.5 mm-wide notch made in the test piece. For the evaluation, the number of breaks was measured when the common logarithm of the energy release rate was 4.3. In Table 1, Examples 1-1 to 1-2 and Comparative Examples 1-2 to 1-3 are shown as index values when the number of breaks until the test piece of Comparative Example 1-1 breaks is set to 100. In Table 2, Example 1-1 is shown as an index value when the number of breaks until the test piece of Comparative Example 1-1 breaks is set to 100, Example 2-1 is shown as an index value when the number of breaks until the test piece of Comparative Example 2-1 breaks is set to 100, and Comparative Example 2-3 is shown as an index value when the number of breaks until the test piece of Comparative Example 2-2 breaks is set to 100. In Table 3, Example 3-1 and Comparative Example 3-2 are shown as index values when the number of breaks until the test piece of Comparative Example 3-1 breaks is set to 100. In addition, the larger the values in Tables 1 to 3, the more cycles it took to break, and the better the resistance to elongation fatigue.
[0069] [Table 1]
[0070] [Table 2] [Table 3] [Table 4]
[0071] *1 Natural rubber: RSS#3 *2 Sorbitan monoester: Sorbitan monostearate, manufactured by Kao Corporation, "Rheodol AS-10V", hydroxyl group number 3 *3 Sorbitol: Kanto Chemical Co., Ltd., hydroxyl group number 6 *4 Carbon black: N234, manufactured by Mitsubishi Chemical Corporation, "DIABLACK N234" *5 Silica: "NIPSIL AQ" manufactured by Tosoh Silica Corporation *6 Antioxidant: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., "Nocrac 6C" *7 Silane coupling agent: Bistriethoxysilylpropyl polysulfide, manufactured by Shin-Etsu Chemical Co., Ltd. *8 Vulcanization accelerator: N-cyclohexyl-2-benzothiazole sulfenamide, Sanshin Chemical Industry Co., Ltd., "Suncerer CM-G" *9 Styrene butadiene rubber: Asahi Kasei Corporation, "Tufden 2000"
[0072] From the results in Table 1, it can be seen that the rubber compositions of the Examples all achieved a high level of both elongation fatigue property and cut resistance. On the other hand, the rubber compositions of the Comparative Examples showed inferior results to the Examples in some of the evaluation items, and it can be seen that it is difficult to achieve both excellent elongation fatigue property and cut resistance. Furthermore, the results in Table 2 show that each sample of the examples containing a specific amount of sorbitan monoester exhibits superior results in both elongation fatigue resistance and cut resistance compared to each sample of the comparative examples that does not contain sorbitan monoester. From the results in Table 3, it can be seen that the rubber compositions of the Examples are able to achieve both high levels of elongation fatigue property and cut resistance, even when the silica content is high. On the other hand, the rubber compositions of the Comparative Examples showed inferior results to the Examples in some of the evaluation items, and it can be seen that it is difficult to achieve both excellent elongation fatigue property and cut resistance. From the results in Table 4, it can be seen that even when the silica content is high, the rubber compositions of the Examples show excellent results in terms of cut resistance, whereas the rubber compositions of the Comparative Examples show results in terms of cut resistance inferior to the Examples. [Industrial Applicability]
[0073] According to the present invention, it is possible to provide a rubber composition having excellent cut resistance while maintaining good elongation fatigue properties. Also, according to the present invention, it is possible to provide a tire having excellent cut resistance while maintaining good elongation fatigue properties.
Claims
1. A rubber component containing 70% by mass or more of natural rubber; A filler containing at least silica; and 0.1 to 2 parts by mass of a cyclic polyol compound having a hydrocarbyl ester group per 100 parts by mass of the natural rubber in the rubber component, The rubber composition has a silica content of 10 to 50 parts by mass based on 100 parts by mass of the rubber component.
2. 2. The rubber composition according to claim 1, wherein the cyclic polyol compound having a hydrocarbyl ester group has two or more hydroxyl groups.
3. The cyclic polyol compound having a hydrocarbyl ester group is represented by the following formula (1): 【Chemistry 1】 [In the formula, A is a hydrocarbyl ester group having 6 to 30 carbon atoms, and X 1 , X 2 , X 3 and X 4 are each independently -OH or -R (wherein -R is -H or -CH 2 OH), with the proviso that X 1 , X 2 , X 3 and X 4 and at least three of the formula (I) are -OH.
4. The rubber composition according to claim 3, wherein the hydrocarbyl ester group-containing cyclic polyol compound is characterized in that the hydrocarbyl ester group portion of A in formula (1) has 12 to 24 carbon atoms.
5. The rubber composition according to any one of claims 1 to 4, wherein the melting point of the cyclic polyol compound having a hydrocarbyl ester group is 40 to 100°C.
6. The rubber composition according to any one of claims 1 to 5, further comprising a linear polyhydric alcohol (excluding glycerol monostearate).
7. The rubber composition according to claim 6, wherein the content of the linear polyhydric alcohol is 0.5 to 6 parts by mass per 100 parts by mass of the natural rubber in the rubber component.
8. The rubber composition according to any one of claims 1 to 7, characterized in that the filler further contains carbon black, and a content of the carbon black relative to a content of the silica is 0.1 to 4 in mass ratio.
9. The rubber composition according to any one of claims 1 to 8, further comprising a silane coupling agent, the content of the silane coupling agent relative to the content of the silica being 0.2 or less in mass ratio.
10. The rubber composition according to any one of claims 1 to 9, further comprising glycerol monostearate.
11. A tire comprising a tread portion comprising the rubber composition according to any one of claims 1 to 10.
12. 12. The tire of claim 11, wherein the tire is a construction vehicle tire.
Citation Information
Patent Citations
Rubber composition and method of its bonding with steel cord by vulcanization
JP1995118457A
Rubber composition and pneumatic tire using the same
JP2006045279A
Rubber composition for tire tread and pneumatic tire
JP2010215854A
Rubber composition for tire tread and pneumatic tire
JP2011026445A
Rubber composition for tire base tread
JP2011184634A
